Business Retention and Expansion (BRE) Programs: Preparing a Written Report of Survey Findings and Recommendations - Henry M. Cothran (EDIS, 2006)
FE657, a 6-page illustrated fact sheet by Henry M. Cothran, is fourth in a series of 10 publications on establishing Business Retention and Expansion programs. It gives guidelines for writing reports that will be read and understood, describing each section and its purpose. Includes references. Published by the UF Department of Food and Resource Economics, November 2006.